Nutritional Composition of Sorrel Chalices (Hibiscus sabdariffa L.) of Green Type and Red -type Sorrel Chalices Consumed in the City of Bongor (Chad) - Makalao, Mouti Marceline; Massamngue, Azlona (Discoveries in Agriculture and Food Sciences, 2025)
Green and red type sorrel calyxes are vegetables consumed by a barn part of the population. The objective of this work aims to determine the nutritional composition of sorrel chalices (Hibiscus Sabdariffa L.) of green type and red -type sorgers consumed in Bongor (Chad) with a view to providing nutritional knowledge on the consumption of these vegetables. Specifically, it is a question of collecting information on green and red type sorrel caly tall In five (5) districts of the city of Bongor and to determine the nutrients of red sorrel calyxes and green sorrel chalices. An investigation was first carried out using survey sheets with 150 people chosen at random. Then, the physicochemical analyzes were carried out such as the determination of water, ashes, proteins, lipids and total carbohydrates. The survey noted the following results: then, the Physicochemical Analyzes Were Carried Out Such as the determination of Water, Ashes, Proteins, Lipids and Total Carbohydrates. The Survey noted the following results: Sorough cultivation is evaluated at 46% for the green type and 33.33% for the red type. Consumption of chalices is 100% for the green type and 96% for red. Green chalices are consumed most often in the form of 80%sauce, in an occasional way at 91%. The consumption of these chalices is much more consumed during the dry season at 76%. The green chalices are used in the form of tea and juice (juice: 57.33% and tea-just: 29.33%). Physicochemical analyzes have shown that red reddish chalices contain (water: 86.34%; ashes: 43.64%and; Proteins: 0.77%), the red -red calyxes contain (water: 5.59%; ashes: 14.67%; proteins: 6.12%, lipids: 0.50%; carbohydrates: 73.12% and energy value: 321.46 kJ), green cost chalices contain (water: 88.34%; ashes: 7.03% and protein: 1.44%), and dry green chalices contain (water: 7.65% ashes: 14.48%; proteins: 5.44%, lipids: 0.89%; carbohydrates: 71.4% and energy value: 315.37 kJ). All these results show that this vegetable is a good source of nutrients that can be made available to the population.